An analytic study for statistics of social type in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research deals with an important and essential subject which is studying The statistics of social type in Syria from analyzing Data of the census 1994,2004  in addition to Data of Syrian family healthysurvey2009,  the research studied the general type ratio and studying population during the years 1994,2004,2009, and studied the social type ratio for population According To age categories and studied the relation between the age of males and females  at first marriage. According  Of married Through studying the tables of horizontal relative structure To age categories from 15 years until 50 years at first marriage in the censuses 1994,2004, so the research has many results such as: - The general type ratio does not change in Syrian Arab republic during the years 1994,2004,2009. - There are differences between the total ratios of  males and females between 1994 and 2004, and between 2004 and 2009. - There are differences between the average age of first marriage of males and females between the censuses 1994,2004,and the Syrian survey of healthy families 2009. دراسة تحليلية لإحصاءات النوع الاجتماعي في سورية يتناول البحث موضوعاً حيوياً وهاماً ألا وهو دراسة إحصاءات النوع الاجتماعي في سورية ، من خلال تحليل بيانات التعدادين 1994 و2004 إضافة إلى بيانات المسح الصحي الأسري 2009، حيث تمت دراسة نسبة النوع العامة للسكان خلال الاعوام 1994 - 2004 – 2009, ودراسة نسبة النوع الاجتماعي للسكان بحسب الفئات العمرية, وتمت  دراسة العلاقة بين أعمار الذكور والإناث عند الزواج الأول, وذلك من خلال دراسة جداول التركيب النسبي الأفقي للمتزوجين بحسب الفئات العمرية من 15 عاماً حتى 50 عاماً عند الزواج الأول في التعدادين السكانيين1994 و2004 وقد كان من نتائج البحث: -لم تتغير نسبة الجنس(النوع)العامة للسكان في الجمهورية العربية السورية خلال الاعوام 1994 و 2004 و 2009. - توجد فروق بين النسب الكلية للذكور والاناث بين 1994 و 2004, وبين 2004 و 2009. - يوجد فروق بين متوسطي سن الزواج الاول للذكور والإناث بين التعدادين والمسح الصحي الأسري 2009 .